(untitled) (Acta Scientiarum. Agronomy, 2022)
This study aimed to evaluate the influence of vegetative canopy height on the agronomic characteristics and grape must and wine physicochemical properties of a ‘Cabernet Sauvignon’ vineyard in an espalier-trained system. The evaluated parameters comprised agronomic characteristics of ‘Cabernet Sauvignon’ grapevines and physicochemical compositions of ‘Cabernet Sauvignon’ musts and wines, as well as their phenolic compositions (anthocyanins, stilbenes, and flavonoids), and impact on wine contents of methoxypyrazines (volatile compounds that impart vegetal or earthy odors to wine, which are considered undesirable in large intensity). To that end, four heights of the vegetative canopy were tested: 60 cm (T1), 80 cm (T2), 100 cm (T3), and 120 cm (T4). The experiment was carried out in a commercial vineyard in the region of “Campanha Gaúcha” (Dom Pedrito, Rio Grande do Sul State, Brazil) during the productive cycles of 2015/16, 2016/17, 2017/18, and 2018/19. The main agronomic parameters were measured: estimated productivity per plant and hectare, and mean weight and number of clusters. All wines were elaborated by the same traditional winemaking methods. The physicochemical analyses of must and wines were performed by infrared spectroscopy using Fourier Transform Infrared Spectrometer (FTIR), and the phenolic analysis by high-efficiency liquid chromatography and UV-Vis spectrophotometry. Methoxypyrazines were quantified using headspace solid-phase microextraction (HS-SPME), followed by gas chromatography-mass spectrometry (GC-MS). The results showed that treatments did not influence agronomic parameters. However, technological maturation (sugar accumulation) had interesting results for plants managed at higher canopy heights, with respective results obtained for wine. Treatments had little influence on individual quantification of anthocyanins, although cycles had a high influence on their profile. The wines had low concentrations of methoxypyrazines and did not differ among treatments.